Dynamic polarization control of Ni electrodes for sustainable and scalable water electrolysis under alkaline conditions - Sanghwi Han; Sungjun Kim; Hye Jin Cho; Jang Yong Lee; Jaeyune Ryu; Jeyong Yoon (Nature Communications)
Abstract Despite the wide array of oxygen evolution reaction active materials revealed thus far, challenges persist in translating their half-cell scale activities into scalable devices with long-term durability. Here, we present a dynamic polarization control for the continuous electrochemical activation of readily available Ni electrode anodes to achieve sustainable and scalable water electrolysis. Periodic application of a reductive potential between high current density cycles (0.5 or 1 A cm–2) is found to promote and maintain the oxygen evolution activity of Ni electrodes via the incorporation of Fe3+ from KOH electrolytes. This transient polarization strategy successfully extends to an anion exchange membrane water electrolysis system, where a cell voltage of approximately 1.8 V is maintained for over 1000 h under 1 A cm–2. The scalability is further verified by the 25 cm2 3-cell stack system, which lasts for 300 h with negligible voltage loss. Ultimately, this work highlights the power of the dynamic polarization strategy to regulate the dynamic nature of the oxygen evolution interface for sustainable and scalable water electrolysis.